2020
DOI: 10.4081/ijfs.2020.8457
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amines content in Fiore Sardo cheese in relation to free amino acids and physicochemical characteristics

Abstract: Fiore Sardo is a Protected Designation of Origin (PDO) cheese produced in Sardinia (Italy) from raw sheep’s milk, presenting risk factors due to an accumulation of Biogenic Amines (BA). A total of 37 Fiore Sardo cheese samples produced in 19 dairy farms were collected from local retail stores to evaluate BA content and its relationship with free amino acids (FAA) and composition. The following were determined for each sample: pH, water activity, composition (moisture, dry matter, NaCl, protein and fat content)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…In the second year, they ranged between 0.3 and 18.4 ppm (mean value 4.5 ppm) for HIM, and between 0.4 and 8.5 ppm (mean value 2.8 ppm) for TYR. The quantity we found was within the levels considered safe for both BAs (Manca et al, 2020). Putrescine ranged between 0.2 and 25.0 ppm (5.8 ppm mean value) and between 0.4 and 7.2 ppm (2.4 ppm mean value), respectively.…”
Section: Samplesupporting
confidence: 63%
See 3 more Smart Citations
“…In the second year, they ranged between 0.3 and 18.4 ppm (mean value 4.5 ppm) for HIM, and between 0.4 and 8.5 ppm (mean value 2.8 ppm) for TYR. The quantity we found was within the levels considered safe for both BAs (Manca et al, 2020). Putrescine ranged between 0.2 and 25.0 ppm (5.8 ppm mean value) and between 0.4 and 7.2 ppm (2.4 ppm mean value), respectively.…”
Section: Samplesupporting
confidence: 63%
“…In the second year, they ranged between 0.3 and 18.4 ppm (mean value 4.5 ppm) for HIM, and between 0.4 and 8.5 ppm (mean value 2.8 ppm) for TYR. The quantity we found was within the levels considered safe for both BAs (Manca et al ., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the increase in BA contents toward the end of the ripening period and the slowing down trend of the decrease in pH levels may be associated with proteolytic activity. In this context, (Gavina Manca et al, 2020) suggested a relationship between the amount of BA and pH values due to the effect of free amino acids resulted from proteolysis.…”
Section: Physicochemical Compositionmentioning
confidence: 99%